Template Nucleotide Moieties Required for De Novo Initiation of RNA Synthesis by a Recombinant Viral RNA-Dependent RNA Polymerase - Kim, Min-Ju (American Society for Microbiology, 2000)
The recombinant RNA-dependent RNA polymerase of the bovine viral diarrhea virus specifically requires a cytidylate at the 3′ end for the de novo initiation of RNA synthesis (C. C. Kao, A. M. Del Vecchio, and W. Zhong, Virology 253:1–7, 1999). Using RNAs containing nucleotide analogs, we found that the N3 and C4-amino group at the initiation cytidine were required for RNA synthesis. However, the ribose C2′-hydroxyl of the initiating cytidylate can accept several modifications and retain the ability to direct synthesis. The only unacceptable modification is a protonated C2′-amino group. Quite strikingly, the recognition of the functional groups for the initiation cytidylate and other template nucleotides are different. For example, a C5-methyl group in cytidine can direct RNA synthesis at all template positions except at the initiation cytidylate and C2′-amino modifications are tolerated better after the +11 position. When a 4-thiouracil (4sU) base analog that allows only imperfect base pairing with the nascent RNA is placed at different positions in the template, the efficiency of synthesis is correlated with the calculated stability of the template-nascent RNA duplex adjacent to the position of the 4sU. These results define the requirements for the specific interactions required for the initiation of RNA synthesis and will be compared to the mechanisms of initiation by other RNA-dependent and DNA-dependent RNA polymerases.